Study on the anti-fatigue activity of chickpea peptide - DONG Jing-ru; MO Jun-ming; WANG Sheng (Shipin yu jixie)
Objective: This study aimed to investigate the anti-fatigue activity of chickpea polypeptide and its anti-fatigue mechanism. Methods: Weight-bearing swimming test, fatigue-related biochemical index analysis and immune activity determination were analyzed in mice. Results: In the weight-bearing swimming test, the swimming time of the chickpea polypeptide-fed group was significantly longer than that of the control group (P<0.01). The test results of biochemical indicators showed that chickpea polypeptide significantly reduced the levels of urea nitrogen and blood lactic acid in the blood of mice, and also significantly increased the contents of liver glycogen, muscle glycogen and insulin (P<0.01). Chickpea polypeptide also significantly improved the activities of superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) and lactate dehydrogenase (LDH). In addition, chickpea polypeptide supplementation improved the immunity by increasing phagocyte activity, stimulating sIgA secretion and reducing proinflammatory cytokines in mice. Conclusion: Chickpea polypeptide has a strong anti-fatigue effect on mice.